CRITICAL PERSPECTIVES ON GENTRIFICATION: A BRIEF REVIEW - Widianto, Hardian Wahyu (Natapraja, 2022)
The trend of the birth of new residential areas in the branding of modern cities, such as Meikarta, also occurs in cities worldwide. People call it: GENTRIFICATION! Like a catastrophe, gentrification always seems to be followed by the emergence of social conflicts. Mass actions are taken to the streets to voice protests against vandalizing gentrification properties, and clashes with officials are carried out for one purpose: against the presence of gentrification. Unfortunately, gentrification research in Indonesia is roughly "useless" for blue-collar workers because it still does not provide any suggestions to face this problem. Rather than researching to celebrate gentrification, research with a Marxist perspective is needed to make a real contribution to urban blue-collar workers constantly haunted by the threat of being evicted from their modest homes.